A case of post-partum hemorrhage and sterilization in the developing world - Crouch, Mark Hughes (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
A woman delivers a term infant vaginally at a district hospital in Papua New Guinea complicated by a retained placenta, uterine inversion and post-partum hemorrhage. A tubal ligation to protect the life of the mother from possibly fatal complications in future pregnancy is suggested, but the couple's cultural beliefs make this a challenge. This case illustrates the impact of post-partum hemorrhage in a developing world context and cultural issues related to sterilization performed in these settings to protect the life of the mother.